ANALYSIS OF PRICES, PROMOTIONS AND PRODUCT QUALITY IN INCREASING SALES IN COMPANIES CONVENIENCE GOODS (Case Study at PT. Tahta Sukses Abadi) - Angkasa, Justine; Priscillia; Tambun Saribu, Holfian Daulat; Hutauruk, Rapat Piter Sony (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to determine the influence of price, promotion and product quality on sales at convenience goods companies. The sample used in this research was customers from convenience goods companies. The type of data used in this research is quantitative data. The nature of this research is descriptive explanatory. The value of the Adjusted R Square coefficient of determination is 0.512, this shows that the ability of the variables Price (X1), Promotion (X2), and Product Quality (X3) explains its influence on Sales (Y) by 51.2%. Meanwhile, the remaining 48.8% is the influence of other independent variables not examined in this research. It was found that the Ftable value was (2.69) and was significant α = 5% (0.05), namely Fcount (34.263) and sig.a (0.000a). This indicates that the research results accept H1 and reject H0, meaning that simultaneously Price, Promotion and Product Quality have a positive and significant effect on Sales. The value of tcount (2.449) > ttable (1.981) is significant 0.016 < 0.05, it is concluded that there is a partially significant negative influence between Price and Sales. The value of tcount (7.146) > ttable (1.981) is significant 0.000 < 0.05 so it can be concluded that there is a partially significant positive influence between Promotion on Sales. The value of tcount (4.665) > ttable (1.981) is significant 0.000 < 0.05, it can be concluded that there is a partially significant positive influence between Product Quality and Sales